BAlN thin layers for deep UV applications. Issue 4 (11th March 2015) - Li, Xin; Sundaram, Suresh; Gmili, Youssef El; Moudakir, Tarik; Genty, Frédéric; Bouchoule, Sophie; Patriarche, Gilles; Dupuis, Russell D.; Voss, Paul L.; Salvestrini, Jean‐Paul; Ougazzaden, Abdallah
<x xml:space="preserve">Abstract</x> In this work, wurtzite BAlN layers with boron composition as high as 12% were successfully grown by MOVPE. The growth was performed at 650 °C and then annealed at 1020 °C. Low temperature growth was used in order to alleviate B‐rich phase poisoning under high TEB/III ratio. The growth was performed by continuous epitaxy as well as by flow‐modulate epitaxy. BAlN single layers with clearly defined X‐ray diffraction peaks were achieved on AlN templates which are appropriate substrates for deep UV devices, as well as on GaN templates to facilitate distinguishing of the XRD peak of BAlN from the substrate peak. The layer demonstrated columnar crystalline features and inherited wurtzite structure from substrates.<inline-graphic xlink:href="ark:/27927/pgjhx9zcgv" content-type="pssa201400199-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Cross‐section STEM image (bright field) of 75 nm thick BAlN layers containing 12% boron taken along the [11−2 0] zone axis. Zone A is lattice‐oriented along c‐axis and zone B has columnar structure; (b) higher magnification image for the top part of the layer; (c) higher magnification image for the film/substrate interface.